THE EFFECT OF GINGER FOR GARGLING ON SALIVARY PROFILE AND IN-VIVO ANTIMICROBIAL ACTIVITY - Fatihah, Nadia Iha; Marfu’ah, Nurul; Mahirotun NS, Anggun; NA, Eldyamarta; Frida SA, Yuna (International Journal of Islamic and Complementary Medicine, 2023)
Infectious diseases have a high incidence rate, especially during the Covid-19 pandemic, caused various efforts to prevent and treatment the infection. One of the effort is use of traditional herbs, Ginger. Ginger is a thibbun-nabawi herb that known to have antimicrobial activity. This study aims to determine the effect of gargling activity with ginger decoction on salivary profile and in-vivo antimicrobial tests. The study was conducted in University of Darussalam Gontor with respondents who experienced mouth ulcerand dental caries. The treatment was divided into 5 groups, positive control, negative control, ginger decoction in 3 concentrations, 10%, 20%, and 30%. The sample used was respondent's saliva obtained by the spitting method. Samples were tested for pH, and volume and incubated in a microbial growth medium to calculate the number of colonies and observations in a microscope for pathogen identification. Influence of salivary profile and colony count before and after treatment tested with T-Test analysis. The results of the pH test showed an increase in the pH value to be more alkaline after being given a solution of gargling, although the pH increase was the smallest in the negative control group and the highest in the ginger group at 30% (p>0.05). Measurements of saliva volume showed a decrease in saliva volume (p>0.05). Differences in the number of colonies before and after treatment in the control group (+) showed significant differences compared to other groups. The minimum decrease in the number of colonies was showed by the Ginger group of 30% with insignificant differences before and after treatment. The antimicrobial activity test showed ginger decoction had a minimum antimicrobial activity due to ginger decoction was not good at diluting secondary metabolites of ginger that have antimicrobial activity